The Influence of Green Hotel Policy and CSR on Interest in Staying at Hotels - Dipa Mulia; Nia Kusuma Wardhani (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to evaluate the influence of Green Hotel Policies and Corporate Social Responsibility (CSR) on consumers' intention to stay at the hotel, considering the mediating role of Trust. The research method employed a questionnaire distributed to 100 respondents who frequently stay at hotels, with data analysis conducted through validity tests, reliability tests, and hypothesis testing. The results indicate that Green Hotel Policies and CSR have a positive and significant influence on the intention to stay, both directly and through Trust. CSR has a more dominant influence (coefficient 0.516) compared to Green Hotel Policies (coefficient 0.318). Additionally, Trust is proven to be an effective intervening variable in strengthening the relationship between Green Hotel Policies and CSR with the intention to stay. These findings support the importance of implementing environmentally friendly policies and sincere, consumer-relevant CSR programs to enhance trust and the intention to stay. This study also highlights differences in consumer perceptions of sustainability practices, where education and clear communication are key to reducing skepticism